Предмет: Алгебра,
автор: robingood34
Помогите решешить
(5a+7b)-70ab
(8a-b)^(2)-64a^(2)
(x-8)^(2)-2x(6-x)^(2)
(c+7)c-(1-c)^(2)
-6(2x-y)^(2)
-y(3x-y)^(2)
Ответы
Автор ответа:
0
(8a-b)^(2)-64a^(2)=64а²-16аb+b²-64a²=b²-16ab
(x-8)^(2)-2x(6-x)^(2)=x²-16x+64-72x+24x²-2x³=25x²-88x-2x³
(c+7)c-(1-c)^(2)=c²+7c-1+2c-c²=9c-1
-6(2x-y)^(2)=-24x²+24xy-6y
-y(3x-y)^(2)=-9x²y+6xy²-y³
(x-8)^(2)-2x(6-x)^(2)=x²-16x+64-72x+24x²-2x³=25x²-88x-2x³
(c+7)c-(1-c)^(2)=c²+7c-1+2c-c²=9c-1
-6(2x-y)^(2)=-24x²+24xy-6y
-y(3x-y)^(2)=-9x²y+6xy²-y³
Похожие вопросы
Предмет: Алгебра,
автор: NovellaKim127
Предмет: Биология,
автор: aliyevafidan2007
Предмет: Физика,
автор: tkachukoleksandra
Предмет: Химия,
автор: olgashokina
Предмет: Математика,
автор: alexandrglushenko